Makna Taqarrub Ilallah Melalui Shalat 40 Di Surau Wadil Mu’minin Kabupaten Padang Pariaman - Sherly; Lubis, Muallim (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2024)
This research is considered important because it found a new understanding of the meaning of Taqorrub through 40 days of prayer by the mursyid of Sattariyah Surau Wadil Mu'minin Kab. Pariaman. The meaning of Taqorrub is generally understood in general, namely that all matters related to worship are part of Taqorrub, while the Surau mursyid relates it to the teachings of the congregation he leads. The aim of this research is to find out the meaning of Taqorrub in the 40 day prayers of the Surau Wadil Mu'minin congregation. This research is field research using a qualitative approach, by explaining and providing a comprehensive description of the meaning of Taqarrub Ilallah through 40 days of prayer. The results of the research show that the meaning of the 40-day taqarrub ilallah prayer is a servant's sincere effort to serve God and obediently carry out all the rituals during the prayer, in order to achieve closeness to God. Another meaning is that prayer is a means of training to care for and maintain harmony with nature, like humans. This prayer is generally performed by the elderly, especially women who are menopausal, because one important condition for carrying out this prayer is that it must not be interrupted for up to 40 days.